Influence of the angle of dental implant placement on the stress-strain state of the jaw - Musiienko , Olha; Parii , Vitalii; Morhun , Oleksii; Koval , Viktor (The Ukrainian Scientific Medical Youth Journal, 2024)
prosthetics on dental implants is a complex and responsible stage of treatment of patients with dental defects. The success of dental implantation depends not only on careful planning and performed surgical intervention in compliance with the requirements of the protocol, but also on the type of load on the dental implant, the choice of orthopedic design and material. Thorough preparation for prosthetics, taking into account the initial clinical situation and individual characteristics of the patient, ensures a full restoration of the dentition defect with reproduction of the chewing function. The parameters of the stress-strain state in the bone tissue around dental implants are of the greatest importance for the effectiveness of prosthetics on implants, especially in the long term of their functioning. Significant power loads of variable amplitude in the jaw lead to resorption of bone tissue and failure of implants as artificial dental prostheses. In this regard, research on modeling the stress-strain state in bone tissue under different loading conditions of implants is relevant. This research presents the results of studying the stress-strain state of the bone-implant system under static loading. Numerical calculations were performed for four installation angles of the implant: 0°, 7°, 15°, and 22°. The solid model of the mandible and the implant model were made in Spaceclaim software, and the stresses were determined using ANSYS Workbench. The results obtained show the effect of the implant placement angle on the distribution of stress fields in the bone tissue and implant. The analysis of the calculation results will help to ensure optimal functioning and durability of dental implants.